Correlation of Sedentary Lifestyle and Interest in Physical Education Learning among Adolescents - Wibisono, I Gusti Ananda Bayu; Birawa, Chandra; Wicaksana, Amrih Ibnu; Priambodo, Anung (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This study determined the correlation between sedentary activities and interest in Physical Education learning in adolescents. Correlational analysis was utilized in this study, with a sample of 33 students obtained using an accidental sampling technique. The research instrument used an ASAQ questionnaire to acquire sedentary activity data and a learning interest questionnaire that had been tested for validity and reliability values of 0.801> 0.60. The results revealed that the sedentary activity of watching videos/DVDs was the highest, with an average duration of 95.09 minutes/day, and the sedentary activity of reading for pleasure was the lowest, with an average duration of 19.91 minutes/day. Meanwhile, the average interest in Physical Education learning is medium. The product-moment correlation test showed that the Pearson correlation value is -0.350, so it can be concluded that sedentary activities and interest in Physical Education learning have a significant negative correlation. The result stated that the highest sedentary activities had the lowest learning interest.